If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ax + 3 = c Reorder the terms: 3 + ax = c Solving 3 + ax = c Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + ax = -3 + c Combine like terms: 3 + -3 = 0 0 + ax = -3 + c ax = -3 + c Divide each side by 'x'. a = -3x-1 + cx-1 Simplifying a = -3x-1 + cx-1 Reorder the terms: a = cx-1 + -3x-1
| 3x+5y=200.4 | | 4-3a+4=0 | | 7x-3(x+2)=4x+3 | | 2(x+5)=4x-(2x-10) | | 6x(4x-3)+20x-24x^2=14 | | 6(2-3x)=5(x+4) | | (a-b)(2a^3-ab+3b^2)=0 | | 11.5(2x-6)=4(3.5x+12) | | 3.5=2.5d+5 | | y^2+27y=0 | | x^5+6x+17=0 | | 2/3x-3/2x=1/12 | | 1/8+2/9 | | (2x+5)(x-9)= | | P=r+s-p | | x^2+36x+27= | | 4a^2-12a-7=0 | | 6-2*7=4x-6x-3 | | 10y+(3y+11)=180 | | 18-6a=12 | | 0=x+7-32 | | 35.00+0.75x=20 | | 5m+6n=64 | | (4+7i)+(-3+5i)=1+12i | | 2a+4b=46 | | 1.25x=25 | | 4t+8s=64 | | x^2+36x+27=0 | | 10y+(7x+4)=180 | | 8s+4t=64 | | 3s+2t=27 | | 2/5x+1=7 |